'Paris with snakes'? The future of communication is/as 'Cultural Science'. (November 2016) - Hartley, John; Potts, Jason
What if communication has been pursuing the wrong kind of science ? This article argues that the physics-based or 'transmission' model derived from Claude Shannon and criticised by James Carey does not explain how communication works. We argue instead for a model derived from the evolutionary and complexity sciences. Here, communication is based on dynamic systems of meaning (not individual 'particles' of information), and relations among knowledge-producing agents in culture-made groups. We call this sign-based evolutionary and systems model of communication 'cultural science' (Hartley and Potts, 2014), and invite communication scholars to assist in its development as a 'modern synthesis' for communication, along the lines of Huxley's synthesis of botany and zoology as evolutionary bioscience.